Acute HIV infection in family - Z. A. Khokhlova; T. N. Lonshakova; T. V. Sereda; M. E. Bataeva (Лечащий Врач, 2024)
Background. Currently, there is an increase in the proportion of HIV-infected women of childbearing age. Infection can occur both before pregnancy, during pregnancy, and in the postpartum period. This creates risks of vertical transmission of the disease from mother to child. If infection of the mother occurs in the postpartum period against the background of lactation, the baby is infected through breast milk. Infants infected perinatally are delayed in development, suffer more often and more severely from opportunistic infections and oncological diseases, and their HIV infection rapidly progresses with the early development of immunodeficiency. Early diagnosis and perinatal prevention of infection are crucial.Objective. To analyze the clinical, epidemiological and laboratory features of acute HIV infection in a mother and perinatally infected infant.Materials and methods. We studied the medical records of an inpatient (form 003/y) and the results of our own clinical observation of the mother and baby who were treated at the Novokuznetsk City Clinical Infectious Diseases Hospital.Results. A case of acute HIV infection in a mother and infant with clinical manifestations is presented. The mother was diagnosed for the first time 8 months after giving birth, the infection was associated with a change of sexual partner during lactation. The child was breastfed from birth. Symptoms of the disease in the child appeared 1 month after the onset of clinical manifestations in the mother, during the time when she stayed in the infectious diseases hospital. The child was diagnosed with HIV infection based on the detection of human immunodeficiency virus RNA in the blood.Conclusion. In the above observation, a vertical route of infection of an infant was realized through the breast milk of a mother infected through sexual contact. The established HIV status of the mother was the reason for testing the child for HIV. The existing risk of infection of women during lactation with subsequent infection of the child during breastfeeding poses the task of organizing their periodic screening for HIV.